2012
DOI: 10.4028/www.scientific.net/msf.717-720.359
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Surface Morphological Defects and Crystallographic Defects in SiC

Abstract: The origins of certain types of micrometer-scale surface morphological defects on SiC epitaxial layers are clarified using X-ray topography. Two types of surface morphological defects are commonly observed on Si- and C-face epitaxial layers. Relatively large pits (around 4μm×2μm) originate from threading screw dislocations (TSDs). Relatively small pits (around 1.5μm×1μm) originate from threading edge dislocations (TEDs). The shapes and depths of these surface morphological pits depend on the fabrication histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…A threading dislocation (TD), which either propagates from the substrate or originates at the emergence point of the substrate, leads to deterioration of device properties such as low breakdown voltage, reverse bias leakage and short life time. 4,5) Although TDs in 4H-SiC have been studied by X-ray topography coupled with etchpitting [6][7][8][9][10][11][12] or cathodoluminescence (CL) method, 13,14) the poor resolution of these methods has directed attention to the application of transmission electron microscopy (TEM). [15][16][17][18][19] Onda et al 19) using TEM have shown that, in addition to a threading edge dislocation (TED) of b ¼ 1=3h11 20i, the socalled threading screw dislocations (TSDs) can be categorized into three types, the Burgers vectors of which being b = [0001], 1=3h11 23i, and h01 11i, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A threading dislocation (TD), which either propagates from the substrate or originates at the emergence point of the substrate, leads to deterioration of device properties such as low breakdown voltage, reverse bias leakage and short life time. 4,5) Although TDs in 4H-SiC have been studied by X-ray topography coupled with etchpitting [6][7][8][9][10][11][12] or cathodoluminescence (CL) method, 13,14) the poor resolution of these methods has directed attention to the application of transmission electron microscopy (TEM). [15][16][17][18][19] Onda et al 19) using TEM have shown that, in addition to a threading edge dislocation (TED) of b ¼ 1=3h11 20i, the socalled threading screw dislocations (TSDs) can be categorized into three types, the Burgers vectors of which being b = [0001], 1=3h11 23i, and h01 11i, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The lattice bending of grown crystals was examined by x-ray rocking curve measurements, which were performed using a double-axis diffractometer, where double crystal x-ray optics for Cu K D1 radiation is employed. The x-ray beam was incident on the (0001)Si or (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) surface of crystals, and the footprint size of the incident x-ray beam on the sample surface was about 1 mm square.…”
Section: Methodsmentioning
confidence: 99%
“…The epitaxial growth was performed in a horizontal hot-wall reactor on 4H-SiC(0001)Si substrates 8˚ off-oriented toward [11][12][13][14][15][16][17][18][19][20]. Silane (SiH 4 ) was used as the silicon source and ethylene (C 2 H 4 ) as the carbon source, with the carrier gas of hydrogen (H 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The 4H-SiC wafers with epitaxy film commercially available in the market were observed by Berg-Barrett X-ray topography, and the terminal end positions of threading-screw dislocations and threading-edge dislocations on the epitaxy film surface were detected. Moreover, we investigated the relationship between the epitaxy film and the surface morphology using an optical microscope, SEM, AFM, and so on [37]. We found some wafers contain pits shown in Fig.…”
Section: Time-dependent Dielectric Breakdown Of Mos Structure and Dismentioning
confidence: 99%